Wolf and Stanley on environmental law - Wolf, Susan; Stanley, Neil (London, Routledge, 2014)
"Written with real clarity by authors teaching and researching in the field, Wolf and Stanley on Environmental Law offers an excellent starting point for both law and non-law students encountering this diverse and controversial subject for the first time. Topics covered include administration and enforcement, EU environmental law, pollution control, waste management, environmental permitting, contaminated land, environmental torts and private regulation. The book is supported by a range of learning features designed to help students:Consolidate your learning: Chapter learning objectives and detailed summaries clarify and highlight key points Understand how the law works in practice: 'Law in Action' features demonstrate the application of environmental lawPlan your research: Detailed end of chapter further reading sections outline articles, books and online resources that provide next steps for your researchThis sixth edition has been updated and revised to take into account recent developments in the subject, including coverage of the Environmental Permitting (England and Wales) Regulations 2010, as well as developments in Environment Agency enforcement and sanctions policy documents and updates relating to the defence of statutory authority in the tort of private nuisance.Suitable for students of environmental law and the wider environmental studies, Wolf and Stanley on Environmental Law is a valuable guide to this wide-ranging subject"--
"Written with real clarity by authors teaching and researching in the field, Wolf and Stanley on Environmental Law offers an excellent starting point for both law and non-law students encountering this diverse and rapidly developing subject for the first time. The focus of the book is on the regulation and control of pollution and includes chapters on environmental permitting, waste management, air and water pollution and contaminated land. The book also includes the administration and enforcement of environmental law, EU environmental law, the environmental torts and the private regulation of environmental law. The book is supported by a range of learning features designed to help students: Consolidate your learning: Chapter learning objectives and detailed summaries clarify and highlight key points Understand how the law works in practice: 'Law in Action' features demonstrate the application of pollution control law Plan your research: Detailed end of chapter further reading sections outline articles, books and online resources that provide next steps for your research This sixth edition has been updated and revised to take into account recent developments in the subject, including coverage of the Environmental Permitting (England and Wales) Regulations 2010; developments in the Environment Agency enforcement and sanctions policy documents; updates relating to the defence of statutory authority in the tort of private nuisance; and current issue relating to compliance with the Aarhus Convention Suitable for students of environmental law and the wider environmental studies, Wolf and Stanley on Environmental Law is a valuable guide to this wide-ranging subject"--
Includes bibliographical references and index.
Keywords: Environmental law -- England; Environmental law -- Wales; LAW / General; LAW / Environmental; LAW / Practical Guides